Jewish History and Memory in Paul Celan's "DU LIEGST" - Irene Fußl (Studies in 20th & 21st Century Literature, 2007)
In the poem "DU LIEGST" (1967), Paul Celan demonstrates his mindfulness of historical dates as memorials to past traumas—the execution of the conspirators of the plot to assassinate Hitler on 20 July 1944, the murder of Karl Liebknecht and Rosa Luxemburg in 1919, and the be-heading of Danton in 1794. Celan has also written the specific date of the poem into the text, although hidden, and weaves together Jewish tradition and events of the recent past in a lyric exploration of human suffering. Building on the hitherto predominantly biographical readings of the poem, the presence of traditional Jewish texts (Old Testament, the Pessach-Haggada, and the Kabbala) and Christian teaching (New Testament) are analysed in "DU LIEGST," to reveal intertextual levels previously untreated by scholarship. Two discordant levels of biblical intertextuality are evident, that of the Old Testament, with trigger words pointing to the events recounted in Genesis, Exodus and Deuteronomy, and also that of the New Testament, based on the story of the Christian Messiah. Evidence of these given pre-texts is discussed with reference to the distinctive characteristics of Hebrew and to linguistic structures employed in the Bible, which point to Celan's debt to Judaism and his mastery of Hebrew. Furthermore a mystic-kabbalist interpretation of the poem reveals a surprising number of symmetrical words, dates, and symbolic numbers.
Keywords: DU LIEGST; Paul Celan; trauma; memory; Karl Liebknecht; Rosa Luxemburg; Danton; Jewish tradition; Jewish texts; biblical intertextuality; Christianity; Judaism; Hebrew